2022
DOI: 10.3389/fpls.2022.974745
|View full text |Cite
|
Sign up to set email alerts
|

Increasing evapotranspiration decouples the positive correlation between vegetation cover and warming in the Tibetan plateau

Abstract: Plant growth generally responds positively to an increase in ambient temperature. Hence, most Earth system models project a continuous increase in vegetation cover in the future due to elevated temperatures. Over the last 40 years, a considerable warming trend has affected the alpine ecosystem across the Tibetan Plateau. However, we found vegetation growth in the moderately vegetated areas of the plateau were negatively related to the warming temperatures, thus resulting in a significant degradation of the veg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 50 publications
0
1
0
Order By: Relevance
“…Trends in vegetation characteristics and climate drivers suggest some decoupling of vegetation growth responses from climate variability. Previous studies have observed negative trends in vegetation growth despite positive climatic trends, indicating a potential decoupling or divergence (Dai et al, 2022;Fu et al, 2015). However, this phenomenon has rarely been considered in the context of time-lag effects.…”
Section: Understanding Vegetation Carryover (Vgc) and Lagged Climatic...mentioning
confidence: 96%
“…Trends in vegetation characteristics and climate drivers suggest some decoupling of vegetation growth responses from climate variability. Previous studies have observed negative trends in vegetation growth despite positive climatic trends, indicating a potential decoupling or divergence (Dai et al, 2022;Fu et al, 2015). However, this phenomenon has rarely been considered in the context of time-lag effects.…”
Section: Understanding Vegetation Carryover (Vgc) and Lagged Climatic...mentioning
confidence: 96%